Genetic and tissue level muscle-bone interactions during unloading and reambulation - Judex, S. (J Musculoskelet Neuronal Interact, 2016)
Little is known about interactions between muscle and bone during the removal and application of mechanical signals. Here, we applied 3wk of hindlimb unloading followed by 3wk of reambulation to a genetically heterogeneous population of 352 adult mice and tested the hypothesis that changes in muscle are associated with changes in bone at the level of the tissue and the genome. During unloading and relative to normally ambulating control mice, most mice lost muscle and cortical bone with large variability across the population. During reambulation, individual mice regained bone and muscle at different rates. Across mice, changes in muscle and trabecular/cortical bone were not correlated to each other during unloading or reambulation. For unloading, we found one significant quantitative trait locus (QTL) for muscle area and five QTLs for cortical bone without overlap between mechano-sensitive muscle and cortical bone QTLs (but some overlap between muscle and trabecular QTLs). The low correlations between morphological changes in muscle and bone, together with the largely distinct genetic regulation of the response indicate that the premise of a muscle-bone unit that co-adjusts its size during (un)loading may need to be reassessed.